Molecular dynamics simulation of diffusion and sorption of water in conducting polyaniline - Ostwal, Mayur M.; Tsotsis, Theodore T.; Sahimi, Muhammad (The Journal of chemical physics, 2007)
Energy minimization and molecular dynamics simulations are used to develop, for the first time, atomistic models of HCl- and HBr-doped conducting polyanilines, in order to study diffusion and adsorption of water vapor in the polymers. Various morphological properties of the polymers are computed, including their pair correlation functions that are found to be in good agreement with the experimental data, and their accessible free volumes. Also computed are the sorption isotherms and effective self-diffusivity of water vapor in the polymers. The computed sorption isotherms are in quantitative agreement with the experimental data, while the diffusivities are within an order of magnitude of the data. The reasons for the differences between the computed and measured diffusivities are discussed.